Juror #3 [compact disc, unabridged] - Patterson, James, 1947-; Allen, Nancy (Lawyer) (Hachette Audio, 2018)
Struggling young attorney Ruby Bozarth defends a man she passionately believes to be innocent in a first murder trial that could make or break her career, only to discover that the case is affected by a juror's shocking secret.